CIRCULAR ECONOMY AND GLOBALIZED WASTE MANAGEMENT - Zvarych, Iryna (Journal of European Economy, 2019)
The analysis of adaptation circular economy according to the principles of 3R (Reduce, Reuse and Recycle) is made and the fourth principle is proposed -global corporate social responsibility (Responsibility), as obligatory in the formation of global circular value added chains. Successful practical examples (startups) of the basic ideas of circular economy implementation are proposed. The circular economy should be considered at the micro, mesa and macro levels, covering production, consumption and proper waste management. Indicators of micro, mesa and macro are evaluated for implementation circular economy. Circular economy as a vector for sustainable development requires a needed shift from linear to circular way of thinking. Circular economy seeks to separate economic growth from using of the natural resources and ecosystems through more effective use of these resources. According to the definition it is a driving force for innovation in the resource and component reuse product that is equivalent to the new business models, particularly in the service sector. Outlined prerequisites that make the circular economy like necessary business model, including the resources and pricing them, the increasing number of middle class, «big data», changing legislation and management, the transition from «agreement» to «relations». It is alleged that the transition to a circular economy means changes in thought and action, which requires a systematic approach and affects how the business model, management, law, logistics, housing, agriculture and other will be organized and structured. Circular economy is a system in which resource flows effectively managed and processed, executed, fully based on renewable energy sources and any action without causing adverse effects on human life and ecosystems within the formation and operation of the global circular value added chain. JEL: Q01, Q56, Q57.